1977
DOI: 10.1007/bf00430954
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of serum glycoproteins the days following a prolonged physical exercise and the influence of physical training

Abstract: Eight male subjects (mean age 24.1 +/- 2.6 years) performed at intervals of 2 weeks successively a 3 h and two 2 h runs of different running speed. The days following the running there were moderate elevations of C-reactive protein, haptoglobin, alpha-1-acid glycoprotein, coeruloplasmin, transferrin, alpha-1-antitrypsin and plasminogen. There were small or no changes of albumin, alpha-2-macroglobulin and hemopexin. The elevations of the "acute phase reactants" were examined in three male subjects following a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0
3

Year Published

1985
1985
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 45 publications
6
47
0
3
Order By: Relevance
“…The level of acute phase protein CRP in plasma was elevated (fourfold) 16 h after the race in both studies. A similar observation was made by Dufaux et al (1984) and Liesen et al (1977), who demonstrated a sixfold increase in the concentration of serum CRP following 2 and 3 h of running, 1 day after the run. These results are consistent with damage to muscle after Statistical significance compared with baseline is denoted by *P = 0.05; **P = 0.01; ***P = 0.001 such severe and prolonged exercise.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The level of acute phase protein CRP in plasma was elevated (fourfold) 16 h after the race in both studies. A similar observation was made by Dufaux et al (1984) and Liesen et al (1977), who demonstrated a sixfold increase in the concentration of serum CRP following 2 and 3 h of running, 1 day after the run. These results are consistent with damage to muscle after Statistical significance compared with baseline is denoted by *P = 0.05; **P = 0.01; ***P = 0.001 such severe and prolonged exercise.…”
Section: Discussionsupporting
confidence: 72%
“…By contrast, the literature is much less prolific on the acute phase reactant responses (Liesen et al 1977, Dufaux et al 1984, 1989a and b and 1991Camus et al 1994) and the metabolic implications (Blomstrand et al 1988;Poortmans et al 1991) involved during prolonged exercise. The present investigation is an attempt to make a link between the lymphocyte changes, some acute phase proteins and cytokine responses and some plasma metabolic implications.…”
Section: Discussionmentioning
confidence: 85%
“…Also, a positive correlation was obtained between the maximum IL-6 and CRP concentrations (r s 0.442 ; P l 0.016). Elevations of positive acute-phase proteins have been reported by others [36][37][38][39]. Dufaux et al [36] and Liesen et al [37] reported 6-fold increases in CRP 1 day after a 2 h or a 3 h run respectively, while a peak may be observed 24 h after strenuous exercise [39].…”
Section: Discussionmentioning
confidence: 77%
“…For example, increased physical effort (e.g. during the nestling rearing period) may raise ceruloplasmin because of inflammatory processes that occur in the muscles (Liesen et al, 1977;Kenyon et al, 2011). Plasma samples were diluted 1:30 and were then analysed according to manufacturer's instructions.…”
Section: Analyses Of Blood Oxidative Statusmentioning
confidence: 99%